Analisis Peran Pedagogis Guru dalam Desain Instrumen Tes Uraian untuk Stimulasi Berpikir Kritis pada Siswa Mata Pelajaran IPAS Sekolah Dasar (SD) - Fauziyyah Azzahra; Aulia Aulia; Salsabila Putri Siregar; Lufia Dwi Yanti; Zulfani Sesmiarni (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the pedagogical role of teachers in designing essay test instruments to stimulate critical thinking skills of fifth-grade students in elementary school science subjects. The study used a literature review method by examining various scientific sources, such as SINTA-indexed national journal articles, textbooks, and relevant research that discuss learning evaluation, test instrument development, and teacher pedagogy. The results of the study indicate that the teacher's pedagogical role significantly determines the quality of essay test instruments, especially in selecting cognitive indicators, compiling contextual stimuli, and selecting operational verbs that are appropriate to the level of critical thinking skills. Teachers who have adequate pedagogical competence are able to design essay test instruments that encourage students to analyze information, provide logical reasons, and develop answers systematically. In addition, HOTS-based essay tests have proven effective in measuring and stimulating critical thinking skills in the context of science learning. This study emphasizes the importance of improving teachers' pedagogical competence in developing evaluation instruments so that the learning process is more meaningful and oriented towards the development of higher-order thinking skills.